ANTENATAL CARE ATTENDANCE AND PARENTAL EDUCATION ARE ASSOCIATED WITH UTILIZATION OF NON-TRAINED DELIVERY ATTENDANTS IN NEGERI LIMA HEALTH CENTER CATCHMENT AREAS, MALUKU PROVINCE - Chistiana Rialine Titaley; Shafira Chaerani; Merlin Maelissa; Filda V. I. de Lima; Alessandra Saija; Yosefina Mainase; Nathalie Kailola; Bertha J. Que (Molucca Medica, 2019)
Introduction Maluku Province was one of the provinces in Indonesia with a high utilization of non-trained delivery attendants during childbirth. The study aims to examine factors associated with utilization of non-trained delivery attendants in the catchment area of Negeri Lima Puskesmas of Leihitu Peninsula in Maluku Province. Methods Data were derived from a household survey conducted in November 2018, in five villages as the catchment areas of Negeri Lima Health Center. Information was collected form 99 mothers who recently delivered in the last six months. Multivariate logistic regression analyses were employed to analyze factors associated with use of non-trained delivery attendants. Results More than 45% of mothers who delivered in the last six months used non-trained delivery attendants at childbirth. A significantly lower odds for using non-trained attendants was found in mothers who graduated from senior high school (aOR=0.23, 95% CI: 0.06-0.83) or academy/university (aOR=0.06, 95% CI: 0.01-0.34) than those graduated from primary school or lower. A similar pattern was found with father’s education. Additionally, the odds of using non-trained attendants reduced significantly amongst mothers attending four or more antenatal care services (aOR=0.34, 95% CI: 0.12-0.96). Conclusions Interventions to promote optimum use of antenatal care and improve community awareness and knowledge about mother and child health care are still essential. Involvement of different types of community members in health promotion activities, in addition to efforts to assign new roles to traditional birth attendants will help to increase the uptake of trained delivery attendants at childbirth amongst mothers in this area. Keywords: education, antenatal care, delivery attendants, Negeri Lima Health Center, Maluku Province